The Utility of Next-Generation Sequencing in Gene Discovery for Mutation-Negative Patients with Rett Syndrome - Gold, Wendy Anne; Christodoulou, John (Frontiers in Cellular Neuroscience, 2015)
Rett syndrome (RTT) is a rare, severe disorder of neuronal plasticity that predominantly affects girls. Girls with RTT usually appear asymptomatic in the first 6-18 months of life, but gradually develop severe motor, cognitive and behavioural abnormalities that persist for life. A predominance of neuronal and synaptic dysfunction, with altered excitatory-inhibitory neuronal synaptic transmission and synaptic plasticity are overarching features of RTT in children and in mouse models. Approximately 95% of patients with classical RTT have mutations in the X-linked methyl-CpG-binding (MECP2) gene, whilst other genes, including cyclin-dependent kinase-like 5 (CDKL5), Forkhead box protein G1 (FOXG1), Myocyte-specific enhancer factor 2C (MEF2C) and Transcription factor 4 (TCF4), have been associated with phenotypes overlapping with RTT. However, there remain a proportion of patients who carry a clinical diagnosis of RTT, but who are mutation negative. In recent years, next-generation sequencing (NGS) technologies have revolutionized approaches to genetic studies, making whole-exome and even whole-genome sequencing possible strategies for the detection of rare and de novo mutations, aiding the discovery of novel disease genes. Here, we review the recent progress that is emerging in identifying pathogenic variations, specifically from exome sequencing in RTT patients, and emphasize the need for the use of this technology to identify known and new disease genes in RTT patients.